Philippines Financial Sector Assessment Program : Capital Markets Regulation and Supervision - Rodriguez, Eddy (World Bank, Washington, DC, 2021)
The securities and exchange commission (SEC) is the main regulator of the capital market in the Philippines, but its resources are insufficient to adequately address its core functions, especially the supervision of capital market participants, and yet it has to address other legal responsibilities unrelated to capital markets. Other agencies also have capital market regulatory responsibilities, creating a fragmented regulatory framework that causes inconsistencies detrimental to the market and to investors’ protection. The existence of regulatory arbitrage, supervisory overlaps, and enforcement gaps evidences the need for an active periodic procedure with other financial system regulators to coordinate supervision activities and review unregulated products, markets, market participants and activities. It should include information sharing and analysis of areas where there may be arbitrage, overlap, gaps, and risks to investor protection and market fairness, efficiency and transparency or other risks to the financial system. A clear and consistent risk-based approach for the SEC supervision of capital market intermediaries is needed. The bank secrecy legislation of Philippines impedes prompt access by the SEC to bank account information.